Squamous cell carcinoma antigen-1/SerpinB3 is an endogenous skin injury response element - Jordan R. Yaron; Shubham Pallod; Sepideh Nezhadi; Holly M. Gildar; Jayda Hylton-Pelaia; Jordan Roberts; Jacquelyn Kilbourne; Kaushal Rege (Proceedings of the National Academy of Sciences, 2025)
The squamous cell carcinoma antigen SerpinB3 is a serum-circulating biomarker of epithelial cancers associated with high metastasis, treatment resistance, and poor prognosis. Despite its clinical significance, the endogenous role of SerpinB3 has remained undefined. Here, we identify SerpinB3 as a mediator of epithelial wound healing. Injury induces SerpinB3 expression in vitro and in vivo in the migrating epidermal tongue; overexpression of the protein promotes epithelial-to-mesenchymal transition–like changes. Recombinant Serpinb3a, the mouse ortholog, enhances re-epithelialization in vitro and accelerates wound closure and collagen remodeling in vivo. These findings reveal a physiological function for SerpinB3 in epithelial repair and suggest that its expression in cancer, chronic wounds, and inflammatory diseases may reflect reactivation of a conserved wound response program—positioning SerpinB3 as a compelling therapeutic target.